Why Men Rape: Perspectives From Incarcerated Rapists in a KwaZulu-Natal Prison, South Africa - Ngubane, Lindokuhle Blessing; Nöthling, Jani; Moletsane, Relebohile; Wilkinson, Abigail; Qulu, Lihle (Frontiers in Psychology, 2022)
Sexual offending is a global problem but is particularly prevalent on the African continent and in South Africa. Childhood experiences related to abuse, alcohol use, and criminal activities in the household and community has been associated with an increased risk for violence perpetration in adulthood. Less is known about sexual violence perpetration, especially in the South African context. In this study, the experiences of incarcerated male perpetrators of rape in South Africa are investigated along with the collective social context and individual childhood experiences that potentially contribute to rape perpetration. Eighteen male perpetrators of rape who were inmates at Westville Correctional Services in KwaZulu Natal, South Africa, were interviewed. The semi-structured in-depth qualitative interviews were transcribed, coded and annotated using an interpretive paradigm and thematic analysis approach. Five main themes emerged from the research and included (1) childhood trauma and adverse events, e.g., an absent father, being raised without parents, exposure to criminal or violent behavior, physical abuse, sexual abuse and poverty, (2) understanding rape, e.g., rape as sex by force and without consent, rape as a violent act, rape as sex with a minor, myths about rape (3) substance abuse, e.g., history of alcohol and drug use, and intoxication during rape perpetration, (4) gender roles and avoiding responsibility, e.g., victim blaming, rape as male prerogative, transactional sex, being framed or set-up, ignoring an ancestral call and (5) recidivism. The findings revealed that all rape perpetrators were exposed to at least one childhood trauma type. Family and community violence and criminality was common. Most participants avoided taking responsibility for their actions and blamed the victim and recidivism/prior convictions were often reported. The findings demonstrate the complex personality dynamic involved in the cycle of abuse and the evolution of criminal behavior, starting as a victim and ending as a perpetrator. The findings also highlight the need for interventions aimed at reducing childhood trauma exposure and improving the social and relational context of those at risk for childhood neglect and abuse.